2021
DOI: 10.3846/tede.2021.15801
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Concomitant Concepts in the Discussion on the Circular Economy: A Bibliometric Analysis of Web of Science, Scopus and Twitter

Abstract: A growing interest in the circular economy, which is seen in the intensification of public discourse, could lead to a danger of blurring the concept and introducing inefficiency in implementing circular economy-based solutions. This study explores the trend in concomitant or accompanying concepts of the discussion about the circular economy themes understanding regarding scientific publications (3,486 publications from Web of Science and Scopus) and popular (non-scientific) domain (represented by 106,504 tweet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
(91 reference statements)
0
2
0
1
Order By: Relevance
“…The use of a single database could result in leaving out important material because of the coverage constraints of a single database (Mirzynska et al, 2021). Therefore, two databases, Scopus and Web of Science (WoS) Core Collection database, were specifically chosen in this study to ensur that high-quality journals can be searched.…”
Section: Analysis Tool and Data Acquisitionmentioning
confidence: 99%
“…The use of a single database could result in leaving out important material because of the coverage constraints of a single database (Mirzynska et al, 2021). Therefore, two databases, Scopus and Web of Science (WoS) Core Collection database, were specifically chosen in this study to ensur that high-quality journals can be searched.…”
Section: Analysis Tool and Data Acquisitionmentioning
confidence: 99%
“…18. Lokta’s law analysis feature of bibliometrix enables users to evaluate the impact of a paper over time by examining its citation count. The feature detects research trends (Mirzyńska et al , 2021). …”
Section: Notesmentioning
confidence: 99%
“…A clear understanding of various CE-related concepts can facilitate the practical implementation of CE initiatives. However, Mirzynska et al (2021) found that there exist conceptual ambiguities about the topic of CE and a gap between the public perception and scientific significance of various concepts. They identified the concomitant concepts of CE from bibliographic databases and Twitter posts aimed at general audiences, and compared the results from these two sources.…”
Section: Circular Economy: An Economic Embodiment Of Sustainable Deve...mentioning
confidence: 99%
“…SNA involves multiple aspects including network structure, actors, and information (Fang & Jia, 2017). The CE context is also related to resources, regenerative processes, waste management, and many other subfields (Mirzynska et al, 2021). To promote academic innovations and advancements in the application of SNA to promote CE, it is essential for scholars to grasp the research status and clarify the correspondence between different functions of SNA and practical challenges associated with circular transition.…”
Section: Introductionmentioning
confidence: 99%